Metabolic Reprogramming of Glioblastoma Cells during HCMV Infection Induces Secretome-Mediated Paracrine Effects in the Microenvironment - Mark A. A. Harrison; Emily M. Hochreiner; Brooke P. Benjamin; Sean E. Lawler; Kevin J. Zwezdaryk (Viruses, 2022)
Glioblastoma (GBM) is an aggressive primary central nervous system neoplasia with limited therapeutic options and poor prognosis. Following reports of cytomegalovirus (HCMV) in GBM tumors, the anti-viral drug Valganciclovir was administered and found to significantly increase the longevity of GBM patients. While these findings suggest a role for HCMV in GBM, the relationship between them is not clear and remains controversial. Treatment with anti-viral drugs may prove clinically useful; however, their results do not explain the underlying mechanism between HCMV infection and GBM progression. We hypothesized that HCMV infection would metabolically reprogram GBM cells and that these changes would allow for increased tumor progression. We infected LN-18 GBM cells and employed a Seahorse Bioanalyzer to characterize cellular metabolism. Increased mitochondrial respiration and glycolytic rates were observed following infection. These changes were accompanied by elevated production of reactive oxygen species and lactate. Due to lactate’s numerous tumor-promoting effects, we examined the impact of paracrine signaling of HCMV-infected GBM cells on uninfected stromal cells. Our results indicated that, independent of viral transmission, the secretome of HCMV-infected GBM cells was able to alter the expression of key metabolic proteins and epigenetic markers. This suggests a mechanism of action where reprogramming of GBM cells alters the surrounding tumor microenvironment to be permissive to tumor progression in a manner akin to the Reverse-Warburg Effect. Overall, this suggests a potential oncomodulatory role for HCMV in the context of GBM.